Grolier student encyclopedia volume 11; Michigan Native Americans,Eastern - Scholastic Library Publishing; Carpenter Clive; Footman Tim; Grimbly Shona; Russell Henry; Sutton Gillian; Turner Matt (Danbury, CT : Scholastic Library Publishing, 2004)
An encyclopedia of brief articles intended for use by elementary school students"
v. 1. Abolitionist Movement--Angola -- v. 2. Animal--Baseball -- v. 3. Basketball--Carroll, Lewis -- v. 4. Carson, Rachel--Connecticut -- v. 5. Conquistadors--Ecology -- v. 6. Economy--Food chain -- v. 7. Football--Harrison, William Henry -- v. 8. Hawaii--Inuit -- v. 9. Inventors and inventions--Longitude -- v. 10. Louisiana--Michelangelo -- v. 11. Michigan--Native Americans, Eastern -- v. 12. Native American, Northwest--Olmec and Toltec -- v. 13. Olympic games--Punctuation -- v. 14. Pyramid--Scientific instruments -- v. 15. Scientist--Tanzania -- v. 16. Taste and smell--Venezuela -- v. 17. Venus--Zoology.
Includes indexes
Keywords: Children's encyclopedias and dictionaries; Encyclopedias and dictionaries